1997
DOI: 10.21273/hortsci.32.3.551e
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Carbohydrate Content in Developing Tomato Fruit

Abstract: The carbohydrate economy of developing tomato fruit is determined by wholeplant source–sink relationships. However, the fate of the imported photoassimilate partitioned to the fruit sink is controlled by the carbohydrate metabolism of the fruit tissue. Within the Lycopersicon spp. there exists a broad range of genetic variability for fruit carbohydrate metabolism, such as sucrose accumulation and modified ratios of fructose to glucose in the mature fruit and increased starch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Starch accumulation may be enhanced by an increase of the main enzyme activity [ADP glucose pyrophosphorylase (ADPGppase)] or of the level of synthesis of the substrate (glucose 6P) ( Robinson et al , 1988 ; Nguyen-Quoc and Foyer, 2001 ); it is also triggered by the amount of sucrose unloaded in the fruit ( D'Aoust et al , 1999 ; N'Tchobo et al , 1999 ), which is higher in cherry tomatoes than in large-fruited cultivars ( Islam and Khan, 2001 ). The presence of the apoplastic cell wall invertase gene lin5 ( Fridman and Zamir, 2003 ; Fridman et al , 2004 ) and of a hexose transporter ( Causse et al , 2004 ), together with the absence of a gene regulating the ADPGppase on chromosome 9 ( Schaffer et al , 2000 ), supports the hypothesis that high starch accumulation in L9 was stimulated by the higher sucrose unloading, and hexose transport within the cells (Ruan et al ., 1995, 1997; Ho, 1996 ; Schaffer et al , 1999 ), as observed in an other study ( Li et al , 2002 ). However, the fact that high starch, but not high soluble contents, were recovered in Lx suggested the involvement of several levels of regulation.…”
Section: Discussionsupporting
confidence: 81%
“…Starch accumulation may be enhanced by an increase of the main enzyme activity [ADP glucose pyrophosphorylase (ADPGppase)] or of the level of synthesis of the substrate (glucose 6P) ( Robinson et al , 1988 ; Nguyen-Quoc and Foyer, 2001 ); it is also triggered by the amount of sucrose unloaded in the fruit ( D'Aoust et al , 1999 ; N'Tchobo et al , 1999 ), which is higher in cherry tomatoes than in large-fruited cultivars ( Islam and Khan, 2001 ). The presence of the apoplastic cell wall invertase gene lin5 ( Fridman and Zamir, 2003 ; Fridman et al , 2004 ) and of a hexose transporter ( Causse et al , 2004 ), together with the absence of a gene regulating the ADPGppase on chromosome 9 ( Schaffer et al , 2000 ), supports the hypothesis that high starch accumulation in L9 was stimulated by the higher sucrose unloading, and hexose transport within the cells (Ruan et al ., 1995, 1997; Ho, 1996 ; Schaffer et al , 1999 ), as observed in an other study ( Li et al , 2002 ). However, the fact that high starch, but not high soluble contents, were recovered in Lx suggested the involvement of several levels of regulation.…”
Section: Discussionsupporting
confidence: 81%
“…Schaffer et al . (1999) and Suzuki et al . (2001) considered that PGI was unlikely to be responsible for the regulation of fructose levels in these two species.…”
Section: Discussionmentioning
confidence: 96%
“…Solanum habrochaites fruit primarily accumulates the disaccharide sucrose, with relatively low levels of hexose (Miron and Schaffer, 1991); however, results from over 50 years ago indicated that its low hexose content is also characterized by an unusually high ratio of fructose to glucose (Davies, 1966). The trait of high fructose to glucose is independently inherited from that of sucrose accumulation (Stommell and Haynes, 1993;Schaffer et al, 1998), and hexose-accumulating tomatoes with an increased ratio of fructose to glucose can be developed (Schaffer et al, 1998). The trait was found to be determined by a major gene, which we termed Fgr (fructose to glucose ratio), and breeding lines of tomato harboring the S. habrochaites Fgr allele (Fgr H ) had a significantly increased level of fructose, accompanied by a decrease in the level of glucose (Levin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the inedible, wild species of tomato have served as a source of genetic variability for improving fruit sugar levels and taste in cultivated tomatoes. For example, the trait of sucrose accumulation, determined by the TIV gene, has been introgressed from Solanum chmiliewskii (Chetelat et al, 1995) and S. habrochaites (Hadas et al, 1995;Schaffer et al, 1998), leading to sucrose-accumulating tomatoes. Genetic traits of increased total hexose levels were introduced from Solanum pennellii (LIN5; Fridman et al, 2000) and S. habrochaites (AGPL1; Petreikov et al, 2006Petreikov et al, , 2009).…”
Section: Introductionmentioning
confidence: 99%